Surface finish of composite resins - Alindogan, Phoebe A.
The purpose of this study is to take a closer look into the surface of a composite resin finished with various finishing devices and to compare this with the surface produced with the celluloid strip. Thirty specimens of composite resins were made in the form of disks and were subsequently finished with the finishing devices selected.